Persepsi Mahasiswa Komunikasi Digital dan Media dalam Peningkatan Kreativitas Berbasis Konten TikTok - Dheo Rizky Ananda; Amiruddin Saleh; Harvia Atika Zahira (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The evolution of social media has transformed digital platforms from mere entertainment outlets into informal learning media that university students utilize to gather references and cultivate creative skills. This study aims to analyze student perceptions of TikTok as a source of creative inspiration, explain the creative processes involved in their digital content production, and examine the role of TikTok in fostering creativity. A qualitative approach with a descriptive case study design was employed. Data were collected through semi-structured interviews, observations, and documentation involving 5 (five) students from the Digital Communication and Media Study Program at the Vocational School of IPB University, selected via purposive sampling. Data analysis was conducted descriptively, utilizing technique triangulation and member checking to ensure validity. The study identified three key findings. First, TikTok serves as a visual reference source, facilitating a shift in student learning patterns from text-based literacy to audiovisual literacy. Second, students develop creative ideas through the "Observe, Imitate, and Modify" (ATM) process, ensuring that references are not merely copied but adapted into more original works. Third, the use of TikTok contributes to enhanced self-confidence, public speaking abilities, and digital storytelling skills, as well as greater fluency and flexibility in generating creative ideas. These findings indicate that TikTok has the potential to serve as an informal learning medium that supports the development of student creativity and communication competence, provided it is utilized critically and productively.